Study on Shear Behavior of Reinforced Concrete Beams Confined with Reinforcing Meshes - Abdulkareem, Bashar F.; Ibrahim, Teghreed H.; Mohammed, Hussein K.; Allawi, Abbas A. (Salehan Institute of Higher Education, 2025)
This study reveals the results of a numerical simulation performed using the ABAQUS/CAE finite element program. The study aimed to provide a simulation model that can forecast the shear behavior of reinforced concrete beams confined with reinforcing meshes. Limited numerical studies have been conducted using geogrid or FRP mesh as shear reinforcement, with limited representation accuracy and limited material quality. The results were compared to published experimental findings in the literature. The finding of the finite element model and the experimental results were highly comparable; consequently, the model was determined to be valid. Following this, the domain of numerical analyses was broadened to include the investigation of many aspects, like the material of reinforcement mesh, the angle of inclination of mesh strip, and the number of mesh strips. The results show that the inclined strip beams gave ultimate loads greater than the beams with vertical strips, where the ultimate load for beams with inclined strips was higher than that for beams with vertical strips by 5.6, 2.5, and 9.4% for beams with geogrid, geotextile, and GFRP mesh, respectively. The smaller the strip width and the larger the number, the better. Beams with inclined strips (45°) gave higher ductility indexes than similar beams with vertical strips. Beams with six strips (width of 50 mm) gave higher ductility indexes than similar beams with four strips (width of 75 mm).